Corynebacterium diphtheriae infection as a dermatological problem - case report and review of the literature - Paulina Cieplewicz; Marta Szymoniak-Lipska; Magdalena Jałowska; Adriana Polańska; Monika Bowszyc-Dmochowska; Hanna Tomczak; Ryszard Żaba; Zygmunt Adamski (Termedia Publishing House, 2019)
We report the case of a 36-year-old male patient with alcohol dependence syndrome who was admitted to the Dermatology Unit with erythroderma of unknown aetiology persisting for approximately 2 years. A considerable degree of deformity and ulceration were noted on the patient's right hand. The patient reported that the abnormalities were due to a fall suffered the year before. The culture of material collected from the ulcer was positive for Staphylococcus aureus, Corynebacterium diphtheriae and Streptococcus dysgalactiae. Following a 10-day course of intravenous clindamycin the ulcer healed successfully. Corynebacterium diphtheriae infection should be considered in the differential diagnosis of skin ulcers, particularly in patients with alcohol dependence syndrome and general immunosuppression.